(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2026)
This paper examines the effects of γ-ray and electron irradiation on the optical properties of MgF2 crystals and ceramics. The samples were irradiated with γ-rays over a wide dose range and with a 4 MeV electron beam in the fluence range of 1014–1015 cm-2. A combination of methods was used to study the opaque ceramic samples, including optical and infrared transmission and reflectance measurements, elemental and phase composition analysis, determination of the crystal structure of the near-surface layer, and scanning electron microscopy. For the first time, a deviation in the stoichiometric composition of the near-surface layer of fluoride materials after irradiation was detected using two independent methods-local elemental analysis using characteristic X-rays and IR spectroscopy. The appearance of oxygen in the surface layer was established, which may be related to radiation-induced processes leading to fluorine loss and changes in the chemical composition of MgF2. The obtained results expand our understanding of the mechanisms of radiation-induced defect formation and modification of the optical properties of MgF2 crystals and ceramics.